2014
DOI: 10.1016/j.bbalip.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 regulation of lipid droplet formation

Abstract: The classical regard of lipid droplets as mere static energy-storage organelles has evolved dramatically. Nowadays these organelles are known to participate in key processes of cell homeostasis, and their abnormal regulation is linked to several disorders including metabolic diseases (diabetes, obesity, atherosclerosis or hepatic steatosis), inflammatory responses in leukocytes, cancer development and neurodegenerative diseases. Hence, the importance of unraveling the cell mechanisms controlling lipid droplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 149 publications
(284 reference statements)
1
87
0
5
Order By: Relevance
“…Our finding that inhibition of iPLA 2 by BEL and FKGK11 reduced CB-induced LD biogenesis indicates that this intracellular PLA 2 contributes to the effect of CB. However, although cPLA 2 has been reported to be relevant to LDs formation induced by diverse PAMPS stimuli and a snake venom inflammatory sPLA 2 25, 47 this intracellular PLA 2 does not participate in the genesis of LDs induced by CB in macrophages. A recent study showed the important role of iPLA 2 in fatty acid metabolism and triacylglycerol formation 62 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our finding that inhibition of iPLA 2 by BEL and FKGK11 reduced CB-induced LD biogenesis indicates that this intracellular PLA 2 contributes to the effect of CB. However, although cPLA 2 has been reported to be relevant to LDs formation induced by diverse PAMPS stimuli and a snake venom inflammatory sPLA 2 25, 47 this intracellular PLA 2 does not participate in the genesis of LDs induced by CB in macrophages. A recent study showed the important role of iPLA 2 in fatty acid metabolism and triacylglycerol formation 62 .…”
Section: Discussionmentioning
confidence: 93%
“…Recently, the inflammatory group IIA sPLA 2 s have emerged as critical regulators of LD formation, as they provide free fatty acids from membrane phospholipids that are crucial for this process, directly regulating assembly of these organelles 25 . In light of this and the fact that CB, a group IIA sPLA 2 , is able to release arachidonic acid 7 , a major fatty acid involved in both LD formation and lipid-mediator production 26, 27 during inflammatory processes, we decided to investigate the ability of CB to induce LD formation and the mechanisms involved in LD formation, as well as 15-d-PGJ 2 production, in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we provide novel data to indicate that sPLA 2 -V is required for efficient phagocytosis of zymosan particles and bacteria by IL-4-treated human macrophages and offer evidence that this requirement may involve generation of LPE, likely at the plasma membrane. In addition to its multiple roles in innate immunity and inflammation, sPLA 2 -V was suggested to participate in the progression of atherosclerosis (84). sPLA 2 -V-modified lowdensity lipoproteins promote foam cell formation, and the enzyme has been found in human atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in eicosanoid generation within any cell type is performed by a superfamily of enzymes collectively known as phospholipase (PL)A 2 due to their ability to release fatty acids from sn-2 position of phospholipids [36]. These enzymes are considered key regulators of LD homeostasis, regulating their formation at different levels [36].…”
Section: Lds Synthesize Inflammatory Mediatorsmentioning
confidence: 99%
“…The first step in eicosanoid generation within any cell type is performed by a superfamily of enzymes collectively known as phospholipase (PL)A 2 due to their ability to release fatty acids from sn-2 position of phospholipids [36]. These enzymes are considered key regulators of LD homeostasis, regulating their formation at different levels [36]. Under stimulation, cytosolic phospholipase A 2 (cPLA 2 ) co-localize with LDs from U937 cells [37] and dendritic cells, the resident macrophage population of the central nervous system [38] in parallel to increased LD formation.…”
Section: Lds Synthesize Inflammatory Mediatorsmentioning
confidence: 99%